An evaluation of the English language placement procedure Sekolah Bahasa dan Pemikiran Saintifik - Wan Chek, Noor Allam; Abd Aziz, Noor Hashima (2000)
The purpose of this study was to evaluate the valiclity of the English Language Placement Procedure (ELPP) which used the SPM English results to place first semester students in either BZ1012 - English for Business and Management II.The ELPP was introduced to replace the English Language Placement Test (ELPT).The subjects were 294 first semester students who got a C5/C6 in their SPM English paper and were placed in BZ1022.The results of the statistical analysis indicated that 79.5% of the students got at least a B- IN BZ1022, students entry qualifications did not affect the grades obtained in BZ1022 and there was a correlation of 0.49 between the marks obtainea in the Coursework and Final Examination.In conclusion, the ElPP is a valid replacement procedure introduced to replace the ELPT.